Effective teachers’ personality in strengthening character education - Lukman Lukman; Marsigit Marsigit; Edi Istiyono; Badrun Kartowagiran; Heri Retnawati; Hanif Cahyo Adi Kistoro; Himawan Putranta (International Journal of Evaluation and Research in Education (IJERE), 2021)
Personality is a silent sedentary nature, which affects the attitudes and behavior of every individual. For a teacher, personality will appear as a hidden curriculum, which affects how to teach and educate. This phenomenological research aimed to interpret the characteristics of effective teachers’ personality in strengthening character education. The participants in this study were 17 elementary, secondary, and high school teachers from nine districts in Indonesia. This participant was selected using purposive sampling technique (teachers who have more than 10 years of teaching experience). Data collection was carried out by interview. Qualitative data analysis was performed using the ATLAS.ti software. The data analysis stages in this study were data coding, data classification, and data interpretation. This study found 12 personality characteristics of teachers that are effective in strengthening character education, include able to behave as friends, able to be roles model, able to understand lessons, discipline, respectful of students, treat students impartially in terms of sanctions, patient, relaxed, willing to pursue life-long learning, master the skill of educating character, not known as fierce teachers, and perceived as joyful teachers. The effective teacher personality can provide understanding and improvement of character education in schools.